Happiness in early childhood - Rita Eka Izzaty (Psychological Research and Intervention, 2018)
This research was conducted based on three considerations. Firstly, childhood is a critical developmental stage that forms the foundation for the psychological well-being and future learning development of children. Secondly, the prevalence of child and adolescent behavioral problems is increasing, assumed to be caused by unhappiness. Thirdly, studies related to happiness in early childhood in Indonesia are still lacking. Therefore, this study aims to explore the meaning, situation, and parties associated with happiness in children. Our study is exploratory using a qualitative approach. The respondents include 51 children aged 4 to 6 years. The research took place in the Special Region of Yogyakarta. We interviewed the respondents and later analyzed the data using content analysis. The latter consist of three coding steps: open coding, axial coding, and selective coding. The results show that, 1) the meaning of happiness refers to positive affects (55%), activities (28.9%), getting something (8.89%), positive physical conditions (4.44%), and affiliation (2.22%), 2) The situations that make children happy are activities (36.61%), learning (11.61%), entertainment (9.82%), and sports (2.62%), 3) The parties who make children happy are families (77.92%), extended families (3.90%), non-family (19.48%), God (1.30%) and toys (1.30%).